New Ways for Cities to Tackle Climate Change - Miller, Alan; Swann, Stacy (International Finance Corporation, Washington, DC, 2018)
Cities, which are home to half of the world’s population, are on the front lines of climate change. Extreme temperatures, storms, and floods have a higher impact in crowded urban areas. And cities in emerging economies will bear an even greater burden of climate change threats. Given their vulnerability, as well as their ability to affect change, cities will be key players in shaping efforts to lessen the impact of climate change. Now a number of new initiatives are helping urban leaders better assess and respond to climate risks.